2018
DOI: 10.1111/tid.13015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of donor and recipient cytomegalovirus serology on long‐term survival of heart transplant recipients

Abstract: Background: Some studies have shown that pre-transplant cytomegalovirus (CMV) serostatus is associated with heart transplant patient survival while others have not.We analyzed the relationship between pre-transplant donor/recipient CMV serostatus and long-term mortality in a retrospective cohort of heart transplant recipients at our center. Methods: Adult (Age >17 years) heart recipients transplanted between July 1985-December 2015 were analyzed. Variables included age, sex, pre-transplant donor (D)/recipie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
4
1
Order By: Relevance
“…While a number of adult studies have evaluated the role of CMV infection on CAV and graft rejection among HTx recipients, few studies have explored the impact of CMV risk status on infection, recurrence, and rejection in the setting of prophylactic VGC among children 10,23,24 . While we observed no difference in overall rejection, CAV or survival among CMV risk‐stratified children, time to first rejection episode was significantly shorter among HR (D + R−) HTx recipients as compared to IR (R+) and LR (D−R−) recipients, despite 6 months of VGC prophylaxis.…”
Section: Discussioncontrasting
confidence: 58%
“…While a number of adult studies have evaluated the role of CMV infection on CAV and graft rejection among HTx recipients, few studies have explored the impact of CMV risk status on infection, recurrence, and rejection in the setting of prophylactic VGC among children 10,23,24 . While we observed no difference in overall rejection, CAV or survival among CMV risk‐stratified children, time to first rejection episode was significantly shorter among HR (D + R−) HTx recipients as compared to IR (R+) and LR (D−R−) recipients, despite 6 months of VGC prophylaxis.…”
Section: Discussioncontrasting
confidence: 58%
“…Across the selected countries, most studies reported rates of CMV infection (ranging from 5.2% to 63.2% within 1 year posttransplant) and CMV disease (up to 19%) (Figure S4), which were consistent with those found in Europe and North America where reported rates ranged respectively, between 7.5% and 65.4% (31 studies) 61–91 and between 0.9% and 23.4% (22 studies) 62–65,68–71,76,79–83,87,89–90,92–96 . In this review, a trend toward lower rates of CMV infection was observed in kidney and liver recipients treated with ganciclovir or valganciclovir as CMV prophylaxis (5.2%–20.6%, n = 5 studies) compared to those only managed with preemptive monitoring (from 25.7% to 50.2%, n = 11 studies).…”
Section: Discussionsupporting
confidence: 83%
“…Several studies reported that donor and/or recipient CMV serology alone was associated with a higher risk of mortality among HSCT [ 38 , 39 ] and SOT patients [ 31 , 40 , 41 ]. On the other hand, Mabilangan et al [ 42 , 43 ] found no association between donor/recipient CMV serology and 10 years mortality among heart or lung transplant recipients. One potential explanation for the similar survival rates of CMV and non-CMV patients in our study may be the limited follow-up time of 1 year, which is comparatively shorter than other analyses of survival which reported outcomes based on extended follow-up periods of 5 years or longer [ 34 36 , 39 , 41 ].…”
Section: Discussionmentioning
confidence: 99%